KREATIVITAS GURU IPS DALAM MENERAPKAN SIKAP SOSIAL SISWA MELALUI PEMBELAJARAN IPS TERPADU DI MTSN 1 MALANG - Nur Nisfu Laily; Lilik Sri Hariani; Sulistyo (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study aims to analyze the creativity of social studies (IPS) teachers in implementing students’ social attitudes through integrated social studies learning at MTSN 1 Malang and to identify the forms of social attitudes developed during the learning process. This research employed a qualitative approach with a case study design. The research subjects consisted of social studies teachers, guidance and counseling teachers, vice principals, and ninth-grade students selected purposively based on their relevance to the research focus. Data were collected through observation, semi-structured interviews, and documentation. The validity of the data was ensured through triangulation, prolonged observation, and member checking, while data analysis used the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings revealed that teachers’ creativity played a significant role in fostering students’ social attitudes through contextual, participatory, and experience-based learning strategies. Teachers implemented various innovative learning methods, such as group discussions, social simulations, role-playing, environmental observation, project-based learning, and the use of audio-visual media. These strategies encouraged students to actively participate in the learning process and internalize social values in everyday life. The study also found that integrated social studies learning contributed to the development of positive social attitudes, including cooperation, tolerance, responsibility, social awareness, discipline, respect, and confidence in expressing opinions. Therefore, integrated social studies learning not only functions as a medium for knowledge transfer but also as an effective means of developing students’ social character and awareness.